Cracks in the Climb: Health Problems Faced in Bouldering - Szymchel, Michał; Grzegorzak, Filip; Cąkała, Marlena; Zajkowska-Sierpniak, Aleksandra; Kozioł, Magdalena; Podgórniak, Kamila (Quality in Sport, 2024)
Bouldering is a distinctive discipline within the broader realm of climbing sports, characterized by its dynamic nature and the absence of ropes, which leads to a higher frequency of falls. This climbing style has seen a surge in global popularity, with an increasing number of indoor bouldering facilities emerging worldwide. Bouldering, regarded by some authors as parkour adapted to vertical terrain, involves more dynamic movements than other climbing disciplines. This contributes to a considerable risk of overuse injuries in specific areas of the upper limbs and traumatic injuries in the lower limbs. Furthermore, bouldering, like other climbing disciplines, presents a risk of nail damage and subsequent fungal infections. In addition to examining injury risks, this review also touches on the issue of airborne chalk dust exposure, a well-documented concern in enclosed spaces during indoor bouldering. Our study aims to consolidate the available information, highlighting the potential health hazards of indoor bouldering, raising awareness of these risks, and underscoring the need for further research to better understand and mitigate these dangers.